Measurement of the B0-B̄0 oscillation frequency Δmd with the decays B0→D−π+ and B0→J/ψK⁎0 - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physics letters, 2013)
The B0-B¯0 oscillation frequency Δmd is measured by the LHCb experiment using a dataset corresponding to an integrated luminosity of 1.0 fb−1 of proton-proton collisions at s=7 TeV, and is found to be Δmd=0.5156±0.0051(stat.)±0.0033(syst.) ps−1. The measurement is based on results from analyses of the decays B0→D−π+ (D−→K+π−π−) and B0→J/ψK⁎0 (J/ψ→μ+μ−,K⁎0→K+π−) and their charge conjugated modes.